A Novel Process for Cadaverine Bio-Production Using a Consortium of Two Engineered Escherichia coli - Wang, Jing; Lu, Xiaolu; Ying, Hanxiao; Ma, Weichao; Xu, Sheng; Wang, Xin; Chen, Kequan; Ouyang, Pingkai (Frontiers in Microbiology, 2018)
Bio-production of cadaverine from cheap carbon sources for synthesizing bio-based polyamides is becoming more common. Here, a novel fermentation process for cadaverine bio-production from glucose was implemented by using a microbial consortium of two engineered Escherichia coli strains to relieve the toxic effect of cadaverine on fermentation efficiency. To achieve controllable growth of strains in the microbial consortium, two engineered E. coli strains grown separately on different carbon sources were first constructed. The strains were, an L-lysine-producing E. coli NT1004 with glucose as carbon source, and a cadaverine-producing E. coli CAD03 with glucose metabolism deficiency generated by modifying the PTSGlc system with CRISPR-Cas9 technology and inactivating cadaverine degradation pathways. Co-culturing these two engineered E. coli strains with a mixture of glucose and glycerol led to successful production of cadaverine. After optimizing cultivation conditions, a cadaverine titer of 28.5 g/L was achieved with a multi-stage constant-speed feeding strategy.